2012
DOI: 10.1111/j.1467-9566.2012.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment, gender and mental health: the role of the gender regime

Abstract: Existing research suggests that gender differences in the effect of unemployment on mental health are related to the different positions and roles that are available for men and women in society and the family; roles that are connected with their different psychosocial and economic need for employment. The aim of this article is to analyse the role of gender in the relationship between unemployment and mental wellbeing in Sweden, representing a gender regime with a similar need for employment among women and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 32 publications
11
113
0
5
Order By: Relevance
“…An international comparison has shown that gender differences in the effects of unemployment on health differ in Ireland and Sweden. This finding suggests that the positions and the roles of men and women in the labor market and in the family are important factors explaining the negative consequences of the negative consequences of unemployment on health (Strandh et al 2013).…”
Section: Employmentmentioning
confidence: 89%
“…An international comparison has shown that gender differences in the effects of unemployment on health differ in Ireland and Sweden. This finding suggests that the positions and the roles of men and women in the labor market and in the family are important factors explaining the negative consequences of the negative consequences of unemployment on health (Strandh et al 2013).…”
Section: Employmentmentioning
confidence: 89%
“…For example, in a study conducted in Sweden and Ireland, men's mental health was more negatively affected by unemployment than was women's mental health in Ireland, although men and women were equally affected in Sweden (Strandh et al, 2013). Such discrepant findings, as well as conflicting conclusions by widely cited meta-analyses (McKee-Ryan et al, 2005;Paul & Moser, 2009), suggest that differences in the relation between unemployment and mental health and well-being among men and women may be accounted for by social and cultural factors.…”
Section: Study Objectivesmentioning
confidence: 93%
“…Taken together, such findings suggest that the environments and contexts within which people live their lives can profoundly influence how men and women of all ages experience the hardship of unemployment (e.g., Strandh, Hammarström, Nilsson, Nordenmark, & Russel, 2013). The contexts and environments of the unemployed in Israel (e.g., Kulik, 2001) are likely to be quite different from those surrounding the unemployed men and women studied by Ensminger and Celentano (1990) in the United States (see also , Vondracek, Ferreira, & Santos, 2010).…”
Section: Psychological Well-being and Unemploymentmentioning
confidence: 93%
“…Paul and Moser (2009) wrote that, despite the fact that the gender dimension is debated on occasion and is not yet fully understood, we should generally expect greater negative effects of unemployment among men than among women. Strandh Hammarström, Nilsson, Nordenmark, and Russel (2012) claimed that context has a major influence on the relationship between unemployment, gender, and mental health; in this study, the context is young Finnish men living in a small town with approximately 70,000 inhabitants.…”
Section: Differences Between Men and Womenmentioning
confidence: 99%